Exploring and Screening Rhizobia Nodulating Forage Legumes of Alfalfa (Medicago Sativa) and Vetch (Vicia Villosa) Growing in Ethiopia - Martsa, A. (Arba Minch University, 2023)
Livestock production in Ethiopia has been constrained by feed shortage, low quality and seasonal fluctuations. The use of high-yielding, good quality and drought-tolerant forage legumes like alfalfa and vetch has been suggested to overcome the feed constraints. These forage legumes fix atmospheric nitrogen when being in symbiosis with rhizobia, but show variations in terms of N2-fixation, calling for exploring the best symbionts. Thus, this study was intended to isolate and screen potential rhizobia nodulating forage legumes alfalfa (Medicago sativa) and vetch (Vicia villosa) growing in Ethiopia. A total of 90 bacterial isolates were obtained from field standing root nodules or from soil by plant trap method. The isolates were evaluated for preliminary symbiotic effectiveness and characterized phenotypically. Simultaneously, soil rhizobia population in the sampling sites were estimated using most probable number (MPN). Among the total isolates, 75 were authenticated as rhizobia. 27% of the isolates were preliminarily highly effective in terms of symbiotic effectiveness and 15% of which performed equivocally or better than artificial N-fertilization. There was significant difference (p < 0.05) between isolates regarding nodulation, shoot biomass and symbiotic effectiveness. Culturally, the isolates were rod shaped, gram-negative and fast-growing with colony morphology varying from 2mm to 5mm and adapted to different eco-physiological conditions. The isolates also metabolized a broader range of carbon and nitrogen sources and tolerated varying concentrations of heavy metals and antibiotics; these would enable them to thrive on marginalized soils. Numerical analysis of 55 phenotypic traits clustered vetch isolates into 3 and alfalfa isolates to 3 phenotypic groups at 70% of similarity coefficient. In general, the isolates were phenotypically diverse and symbiotically efficient rhizobia nodulating forage legumes vetch and alfalfa. According to symbiotic effectiveness tests, the rhizobial isolates VB23, VL40, VB76, VK33, VL11, VL34, VB63, AD50, AK88, AB20, and AB60 had high N2-fixation efficiency and are recommended for field evaluation under different environmental conditions. We also recommend those strains for molecular characterization and use as inoculants on sympatric forage legumes in soils where they perform best.